Optimization of the ASKIA CERIA Program in the Process of Issuing Child Identity Cards in Langkat Regency - Elviza, Elviza; Jamaluddin, Yanhar; Siregar, Nina Siti Salmaniah (Journal of Public Representative and Society Provision, 2025)
The ASKIA CERIA (Smart and Friendly Child Population System Application) program is an innovative population administration service designed to accelerate the process of issuing Child Identity Cards (KIA) in Langkat Regency. This research aims to analyze the implementation of the ASKIA CERIA program, identify the challenges faced, and evaluate optimization strategies that can be carried out. A qualitative descriptive approach is used in this study with data collection techniques through interviews, observations, and documentation. The results show that the implementation of ASKIA CERIA in the issuance of KIA in the Disdukcapil of Langkat Regency still faces challenges in aspects of communication, resources, disposition, and bureaucratic structure. Improvement efforts are needed to improve communication strategies, the quality of human resources, budget allocation, motivation for implementers, as well as cross-level coordination and flexibility of procedures so that the program can run more optimally and the benefits are felt by the community. To overcome these challenges, optimization strategies include digital literacy training, improving technological infrastructure, and adding human resources. This study concludes that the digitization of public services through programs such as ASKIA CERIA can be a solution to improve service efficiency, as long as it is accompanied by an inclusive approach and adequate infrastructure support. This finding is expected to be a reference for the development of similar innovations in other regions.